(untitled) (International Journal of Nursing Education, 2025)
Objective: To determine the effect of foot and back massage on hemodynamic stability in chronic kidney disease (CKD) patients undergoing hemodialysis. Hemodynamic stability is essential for patients undergoing hemodialysis, as electrolyte disturbances and hypertension significantly impact their clinical outcomes. This study hypothesizes that foot and back massage could serve as effective non-pharmacological interventions to improve hemodynamic parameters, addressing an area with limited research evidence and aiming to enhance patient care. Material and Method: This study used pre-test and post-test method with non-equivalent control-group design, involving 46 patients divided into 2 groups, intervention group and control group (received routine care). The intervention began with a screening process and pre-test in both intervention and control groups. After the initial assessment, the intervention group began to receive the first intervention session. Foot and back massage interventions were carried out 6 times for 6 days with a duration of 13-15 minutes. Respondents in the control group received routine care.After completing six intervention sessions,post-test was conducted to assess changes in hemodynamics (systolic and diastolic blood pressure, heart rate, respiratory rate, and oxygen saturation). Results: There was a significant difference after the foot and back massage intervention on hemodynamics stability (Systolic and diastolic blood pressure, heart rate (HR), respiratory rate (RR), oxygen saturation (SPO2) before and after the intervention, with p < 0.05. Conclusion: There is a significant effect of foot and back massage interventions on hemodynamic stability (Systolic and diastolic blood pressure, heart rate, respiratory rate, oxygen saturation) in CKD patients undergoing hemodialysis